The Carbon Emission Liability Mechanism A New Solution for Global Carbon Neutrality - Yang, Baoming; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2025)
This open access book presents a novel Carbon Emission Liability Mechanism (CELM) and an integrated global Carbon Pricing Mechanism, based on a comprehensive analysis of the evolution of economic theory related to global climate change and the practice of carbon pricing instruments over the past 30 years. It further outlines a top-level design and implementation blueprint global based on CELM to achieve global carbon neutrality. For the first time, the CELM mechanism effectively addresses the three fundamental questions regarding carbon emissions: who should be liable for carbon emission, how much liability, and how to offset it. The introduction of CELM may unveil a feasible third path towards global carbon neutrality, and effectively address numerous challenges of carbon tax and Emission Trading System. CELM facilitates the creation of an efficient, cost-effective and comprehensive societal carbon footprint database, and addresses issues related to international carbon border regulation mechanism. While the world is struggling to tackcle the imminent climate crisis, CELM offers a refreshing global carbon neutrality solution, with its characteristics of more fair, more efficient, and less expensive, bringing new alternative options for the international community.
Goals, Progress, Issues and Challenges of Global Carbon Neutrality -- Philosophical, Sociological and Legal Discussions on Global Climate Issues -- Current Development and Practice of Climate Change Economics -- The Origin of Global Climate Issues -- New Carbon Emission Liability Mechanism -- National Decarbonization System and Implementation Plan Based on CELM -- Carbon Ticket Management System (CTMS) -- Negative Carbon Market -- Operation Analysis of CELM Decarbonization System -- Global Carbon Neutrality Solutions -- Macroeconomic Effects of CELM System Implementation: An evidence from China -- The Necessity, Feasibility and Urgency of Implementing the CELM System in China.-Suggestions on Dual Carbon Policy and Action to the Chinese Government -- Principles of New Public Goods -- Frequently Asked Questions (FAQ) for CELM Theory and Solutions -- Afterword: The Greatest Truth Lies in a Precise and Straightforward Pathway -- Acknowledgements -- Reference -- Appendix.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Power resources; Environmental economics; Resource and Environmental Economics